Bedside veno‐venous ECMO cannulation: A pertinent strategy during the COVID‐19 pandemic. Issue 6 (12th June 2020) - Calcaterra, Domenico; Heather, Beth; Kohl, Louis P.; Erickson, Heidi L.; Prekker, Matthew E.
Abstract: Background: Patient selection and cannulation arguably represent the key steps for the successful implementation of extracorporeal membrane oxygenation (ECMO) support. Cannulation is traditionally performed in the operating room or the catheterization laboratory for a number of reasons, including physician preference and access to real‐time imaging, with the goal of minimizing complications and ensuring appropriate cannula positioning. Nonetheless, the patients' critical and unstable conditions often require emergent initiation of ECMO and preclude the safe transport of the patient to a procedural suite. Aims: Therefore, with the objective of avoiding delay with the initiation of therapy and reducing the hazard of transport, we implemented a protocol for bedside ECMO cannulation. Matherial and Methods: A total of 89 patients required ECMO support at Hennepin County Medical Center between March 2015 and December 2019. Twenty‐eight (31%) required veno‐venous support and were all cannulated at the bedside. Overall survival was 71% with no morbidity or mortality related to the cannulation procedure. Conclusion: In the current pandemic, the strategy of veno‐venous bedside cannulation may have additional benefits for the care of patients with refractory acute respiratory distress syndrome due to coronavirus disease‐2019, decreasing the risk of exposure of health care worker or other patients to the novel severe acute respiratory syndrome coronavirus‐2 occurring during patient transport, preparation, or during disinfection of the procedural suite and the transportation pathway after ECMO cannulation.